Do Exchange Rate Series Present General Dependence? Some Results using Recurrence Quantification Analysis - Aparicio, Teresa; ., Dulce Saura (Journal of Economics and Behavioral Studies, 2013)
In this paper, we apply a methodology based on the â€œRecurrence Quantification Analysisâ€ to four daily exchange rate returns series. Our aim is to discover if they exhibit some kind of underlying structure, and to find an economic explanation for the behavior of exchange rates. Our results show the existence of structure in all series that, in certain cases, can be identified as non-linear deterministic. We also conclude that, in general, the underlying structure tends to disappear in the most recent periods.